Coronavirus disease 2019 (COVID-19) related cytopenia: A protocol for systematic review and meta-analysis. Issue 36 (4th September 2020) - Li, Yiwei; Weng, Qianping; Huang, Xilian; Xie, Yaping; Chen, Can; Qian, Shenxian
Abstract: Background: In December 2019, the novel coronavirus pneumonia was detected in Wuhan and named COVID-19. It is an international outbreak of the respiratory illness caused by severe acute respiratory syndrome coronavirus 2. Recent papers pointed out the cytopenia in COVID-19 patients including lymphopenia, neutrophilia, thrombocytopenia and lower level of hemoglobin had prognostic significance. This systemic review and meta-analysis summaries the latest evidence from available data and determine the hematological abnormality caused by severe acute respiratory syndrome coronavirus 2 and potential efficacy on the outcomes in patients with COVID-19. Methods: This protocol for a systematic reviews and meta-analysis will be performed according to the preferred reporting items for systematic reviews and meta-analysis protocols 2015 guidelines. The database of Cochrane Library, PUBMED, EMBASE, Medline, Web of Science, Google Scholar, CNKI, WanFang, as well as gray literatures from the inception to present will be comprehensively and systematically searched without limitations of regions or language. The main study outcomes will be the mortality of COVID-19 patients. The meta-analysis was performed by RevMan V.5.3 program and Stata V.12.0 software after 2 reviewers independently selected literature, data extraction, bias risk evaluation and study quality assessment. Any disagreement will be resolved by consensus to the third researcher. Results: This systematic review and meta-analysis may help provide clarify on the effect of cytopenia in patients with COVID-19. The result will be published at a peer-reviewed journal. Conclusions: This proposed study will evaluate the existing evidence on the effectiveness of cytopenia in COVID-19 patients. Ethic and dissemination: The content of this article does not involve moral approval or ethical review because no individual data will be collected. PROSPERO registration: CRD42020187524.